Internalisasi Nilai Tauhid Sebagai Pilar Pendidikan Islam Transformatif - Dul Wahid Toha; Eman Puroman; Fenty Setiawati (Journal of Education and Social Culture, 2025)
Transformative Islamic education emphasize the formation of a whole person rooted in divine values. The value of monoteism as the core of Islamic teachings has great potencial in forming the character and spiritual awareness of students. This study aims to explore the meaning and Strategies for internalizing the values of monotheism in the context of transformative Islamic education, the Method used is qualitative with a literature study of the works of classical and contemporary scholar and islamic education documents. The result of the study show that the value of monotheism is not only a theological concept but also an ethical, social, and pedagogical foundation in forming students who are faithfull, knowledgeable and have noble moral. Internalization of these values can be done through integration in the  curriculum of exemplary educators and a spiritual and collaborative learning environment. Education based on the values of monotheism has an important role in creating social change and civilized civilization.